Facile Synthesis and Characterization of MnO2/Graphene/Multi Walled Carbon Nanotube Nanostructured Ternary Composite: An Advance Material for Environmental and Biological Applications. (2017) - Venkatesh, T.; Mahesh, K.R. Vishnu; Mylarappa, M.; Siddeswara, D.M.K.; Raghavendra, N; Kumar, M.S. Shiva; Rangappa, Dinesh; Prasanna, D.S
Abstract: The present research was mainly focused on an efficient approach for the synthesis of MnO2 /Graphene/Multiwalled carbon nano tubes/nanocomposite (MnO2 /Graphene/MWCNTs). The MnO2 /Graphene/MWCNTs nanocomposite was characterized by using X-Ray Diffracto meter (XRD), Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR) spectra, Ultraviolet-visible (UV-vis) absorption spectra. The morphology of the Nanocomposite (MnO2 /Graphene/MWCNTs) demonstrated that the MnO2 with a nanometer size were uniformly and compactly deposited on Graphene/MWCNTs. As prepared ternary composite material was employed to degrade the high concentration of nonvolatile dyes such as Indigo carmine (IC) and Rhodamine B (RB).The ternary nanocomposite showed synergistic effect on antibacterial activity against Escherichia coli and Staphylococcus aureus.